2021
DOI: 10.1073/pnas.2114442118
|View full text |Cite
|
Sign up to set email alerts
|

Gliding motility of Plasmodium merozoites

Abstract: Plasmodium malaria parasites are obligate intracellular protozoans that use a unique form of locomotion, termed gliding motility, to move through host tissues and invade cells. The process is substrate dependent and powered by an actomyosin motor that drives the posterior translocation of extracellular adhesins which, in turn, propel the parasite forward. Gliding motility is essential for tissue translocation in the sporozoite and ookinete stages; however, the short-lived erythrocyte-invading merozoite stage h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 64 publications
1
47
0
Order By: Relevance
“…Recent imaging of CRISPR Cas9 engineered parasite lines with fluorescent tags ( Lee et al., 2019 ), has boosted the study of specific ligand-receptor interactions at the molecular level. This has permitted the localisation of apical ligands that take part in the invasion ( Treeck et al., 2009 ), and showed that the invasion proceeds with the wider end of the merozoite leading, rather than the narrower pointed end, highlighting a remarkable motion of the merozoite that until now was mostly overlooked ( Yahata et al., 2021 ). Moreover, machine learning algorithms for image recognition have been employed to automatically detect infected cells and their stage ( Davidson et al., 2021 ).…”
Section: Section 1: Mechanics Of Red Blood Cell Invasionmentioning
confidence: 99%
“…Recent imaging of CRISPR Cas9 engineered parasite lines with fluorescent tags ( Lee et al., 2019 ), has boosted the study of specific ligand-receptor interactions at the molecular level. This has permitted the localisation of apical ligands that take part in the invasion ( Treeck et al., 2009 ), and showed that the invasion proceeds with the wider end of the merozoite leading, rather than the narrower pointed end, highlighting a remarkable motion of the merozoite that until now was mostly overlooked ( Yahata et al., 2021 ). Moreover, machine learning algorithms for image recognition have been employed to automatically detect infected cells and their stage ( Davidson et al., 2021 ).…”
Section: Section 1: Mechanics Of Red Blood Cell Invasionmentioning
confidence: 99%
“…CLAMP may also participate in the gliding motility of merozoites, which has recently emerged as an important precursor step during invasion of erythrocytes (Yahata et al, 2021). While TRAP is not expressed in merozoites and, unlike CLAMP, is dispensable for Plasmodium blood stage growth, merozoites express two members of the TRAP protein family, the merozoite thrombospondin-related anonymous protein (MTRAP) and the Plasmodium thrombospondin-related apical membrane protein (PTRAMP) (Baum et al, 2006; Morahan et al, 2009; Thompson et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…CLAMP may also participate in the gliding motility of merozoites, which has recently emerged as an important precursor step during invasion of erythrocytes (Yahata et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the requirements for PfACT1 sequestering and subsequent turnover of F-actin may vary dependent on the process at hand. This can be realised by the varying speeds in motility in different stages of parasites; ookinetes move at 5 µm/min (Kan et al, 2014; Vlachou et al, 2006; Vlachou et al, 2004), merozoites are the next fastest at 36 µm/min (Yahata et al, 2021), whilst the fastest are sporozoites which can reach speeds of 60-120 µm/min (Hopp et al, 2015; Ripp et al, 2021).…”
Section: Discussionmentioning
confidence: 99%